Peranana Manajemen Aset Dalam Meningkatkan Vitalitas Pemerintahan Daerah Otonom - Wirijadinata, Jat Jat (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2007)
Most of the local official more concerned with the financial aspects than the assets of the organization, even one rupiah than the million worth of one asset. Lannd, buildings and islands stay ian peace until they get lost or damaged. The procurements do not always backed up by the maintenance and repair budget sufficiently. Most of the new officials who are posted in new regions have difficulties in housing problems. Are pointed out by NAO (National Audit Office), the main problems faced by public institutions in assets management are: weakness in assets management, poor commercial sense in the existing assets and poor project management.